A Simple Method of VNTR D1S80 Locus Allelic Ladder Construction for Capillary Electrophoresis‐based Genotyping1. Issue 2 (10th July 2017) - Jung, Ju Yeon; Kim, Su‐Ji; Oh, Yu‐Li; Lim, Si‐Keun; Lee, Yang Han; Hwang, Jung Ho
Abstract: VNTR D1S80 locus genotyping has been largely replaced in forensics by STR. As the statute of limitations on murder cases was abolished in the Republic of Korea in July 2015, the demand for re‐analysis of DNA from unresolved murder cases has increased. The National Forensic Service includes several recorded D1S80 genotypes as crucial clues. Here, we re‐established the D1S80 analysis system using capillary electrophoresis and confirmed the reproducibility of the system by comparison with the genotypes of eight DNA samples that had been analyzed using PAGE in 2006. In addition, we created an allelic ladder via new methodology using flanking region sequences. A single DNA sample (K562) and seven primers were used for the new ladder, which contains 12 alleles. Although artificial owing to the use of the flanking region rather than repeat unit reduction, the method is rapid and simple, and could be applicable in any laboratory.